2015
DOI: 10.5861/ijrse.2015.971
|View full text |Cite
|
Sign up to set email alerts
|

Intercultural communicative competence, language proficiency, and study abroad

Abstract: Numerous students are encouraged to study overseas in the hope of becoming competitive professionals in a global community. The two major benefits of studying abroad as commonly believed are foreign language acquisition and intercultural communicative competence development. To gain a deeper understanding of whether study abroad programmers have significantly positive impact on students' linguistic gains and development of intercultural communicative competence, this paper reviews recent research on the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The guided interventions mentioned earlier offer exciting opportunities to facilitate students' negotiation of an intercultural identity. Instead of simply sending students abroad to dissect their intercultural development, which really only happens for students who go abroad for eight months or more (Guo, 2015), programs can offer varying approaches to help navigate the questions that arise about one's own identity in the context of other cultures. The options for these interventions' designs can be crafted to meet students' needs, as well as the program's learning outcomes.…”
Section: Solutions and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The guided interventions mentioned earlier offer exciting opportunities to facilitate students' negotiation of an intercultural identity. Instead of simply sending students abroad to dissect their intercultural development, which really only happens for students who go abroad for eight months or more (Guo, 2015), programs can offer varying approaches to help navigate the questions that arise about one's own identity in the context of other cultures. The options for these interventions' designs can be crafted to meet students' needs, as well as the program's learning outcomes.…”
Section: Solutions and Recommendationsmentioning
confidence: 99%
“…The research thus far has indicated the transformative power of intentional pedagogy in both enhancing students' intercultural competence in study abroad and making that gained competence last beyond the abroad experience. Importantly, these interventions particularly aid students who partake in short-term programs, where intercultural competence does usually not occur (Guo, 2015). As seen, the options available for what these guided interventions might look like can vary greatly.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…The terms ICC (Byram, , 2000), languaculture (Agar, , ), intercultural sensitivity (Bennett, ), cross‐cultural awareness, and regional competence (Watson et al, ) have all been used to describe the ability of learners to communicate with people from other cultures (Deardorff, ; Fantini, ; Guo, ; Sercu, ). Drawing on ICC literature, Sercu et al () described ICC as:
The willingness to engage with foreign culture, self‐awareness and the ability to look upon oneself from the outside, the ability to see the world through the others' eyes, the ability to cope with uncertainty, the ability to act as a cultural mediator, the ability to evaluate others' point of view, the ability to consciously use culture learning skills and to read the cultural context, and the understanding that individuals cannot be reduced to their collective identities.
…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these interventions particularly aid students who partake in short-term programs, where intercultural competence does usually not occur (Guo, 2015). As seen, the options available for what these guided interventions might look like can vary greatly.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Instead of simply sending students abroad to dissect their intercultural development, which really only happens for students who go abroad for eight months or more (Guo, 2015), programs can offer varying approaches to help navigate the questions that arise about one's own identity in the context of other cultures. The options for these interventions' designs can be crafted to meet students' needs, as well as the program's learning outcomes.…”
Section: Solutions and Recommendationsmentioning
confidence: 99%